In Vitro and In Vivo Evaluation of Carbopol 71G NF-Based Mucoadhesive Minitablets as a Gastroretentive Dosage Form - Rump, Adrian; Tetyczka, Carolin; Littringer, Eva; Kromrey, Marie-Luise; Bülow, Robin; Roblegg, Eva; Weitschies, Werner; Grimm, Michael (Molecular pharmaceutics, 2023)
Gastroretentive dosage forms are intended to stay inside the stomach for a long period of time while releasing an active pharmaceutical ingredient. Such systems may offer significant benefits for numerous drugs compared to other sustained release systems, such as improved pharmacokinetics/bioavailability and reduced intake frequency and thereby improved adherence to the medical therapy. However, there is no gastroretentive product on the market with proven reliable gastroretentive properties in humans. A major obstacle is the motility pattern of the stomach in the fasting state in humans, which reliably ensures gastric emptying of even large indigestible objects into the small intestine. One promising approach to avoid gastric emptying is adhesion of the drug delivery system to the gastric mucosa. In order to achieve mucoadhesive properties, minitablets containing Carbopol 71G NF were developed and compared to minitablets without adhesive properties. In a specialized mucoadhesive test system, the adhesion time was prolonged for adhesive minitablets (240 min) compared to non-adhesive minitablets (30 min). The in vivo transit behavior was investigated using magnetic resonance imaging in 11 healthy volunteers in fasted state in a crossover setup. It was found that the gastric residence time (GRT) of the adhesive minitablets (median of 37.5 min with IQR = 22.5-52.5) was statistically significantly prolonged compared to the non-adhesive minitablets (median of 7.5 with IQR = 7.5-22.5), indicating a delay in gastric emptying by adhesion to the gastric mucosa. However, the system needs further improvement to create a clinical benefit. Furthermore, it was observed that for 9 of 22 administrations (three minitablets were given simultaneously with every administration), the minitablets were not emptied together but showed different GRTs.